2013
DOI: 10.1096/fj.13-235176
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental asthma using a single small molecule with anti‐inflammatory and BK channel‐activating properties

Abstract: Large conductance voltage- and calcium-activated potassium (BK) channels are highly expressed in airway smooth muscle (ASM). Utilizing the ovalbumin (OVA) and house dust mite (HDM) models of asthma in C57BL/6 mice, we demonstrate that systemic administration of the BK channel agonist rottlerin (5 μg/g) during the challenge period reduced methacholine-induced airway hyperreactivity (AHR) in OVA- and HDM-sensitized mice (47% decrease in peak airway resistance in OVA-asthma animals, P<0.01; 54% decrease in HDM-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…4 and 5). The unequivocal effect of rottlerin on BKCa channels was also recently demonstrated to alleviate asthma and improve bronchodilation (an important role of BKCa in airway smooth muscle) in WT mice but not BKCa KO animals (15). Collectively, these results indicate that the cardioprotective effects of rottlerin are mediated by BKCa channel activation and that rottlerin may be one of the most promising small molecules available to activate myocardial BKCa channels in vivo.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…4 and 5). The unequivocal effect of rottlerin on BKCa channels was also recently demonstrated to alleviate asthma and improve bronchodilation (an important role of BKCa in airway smooth muscle) in WT mice but not BKCa KO animals (15). Collectively, these results indicate that the cardioprotective effects of rottlerin are mediated by BKCa channel activation and that rottlerin may be one of the most promising small molecules available to activate myocardial BKCa channels in vivo.…”
Section: Discussionmentioning
confidence: 67%
“…Early evidence indicated that the cardioprotective effect of rottlerin was mediated by BKCa channels as demonstrated by pharmacological inhibition of the channel with paxilline. In addition, rottlerin can directly activate BKCa channels as demonstrated by stimulation of in vitro and smooth muscle BKCa currents and rottlerin-induced smooth muscle relaxation (13,15,38,41). In addition to displaying superior potency, rottlerin lacks many of the detrimental side effects seen with the most commonly used BKCa activators, NS11021 and NS1619 (6, 36, 41).…”
mentioning
confidence: 99%
“…However, given the literature that rottlerin can activate the channel in numerous in vitro patch clamp experiments and in vivo studies [12][13][14][15], we feel that the most plausible explanation remains direct activation of the channel. Nevertheless, caution should be taken in interpretation to include the possibility of indirect vasodilatory effects that are dependent on BKCa activity.…”
Section: Commentmentioning
confidence: 88%
“…Zacharov and colleagues [12] and Goldklang and colleagues [13] demonstrated through patch clamp studies that rottlerin can leftward shift voltage dependent activation of the channel approximately 70 mV. Goldklang and colleagues also [13] recently demonstrated in vivo that rottlerin can reduce airway smooth muscle hyper responsiveness in a BKCadependent manner in asthma models. Others have demonstrated rottlerin as a potent BKCa activator in cell lines and in vitro studies [14][15][16].…”
mentioning
confidence: 99%
“…This wide distribution is associated with an outstandingly large functional diversity, in which BK channel activity appears optimally adapted to the particular physiological demands of each cell type (2). On the other hand, small alterations in BK channel function may contribute to the pathophysiology of hypertension, asthma, cancer, epilepsy, diabetes, and other conditions in humans (3)(4)(5)(6)(7)(8). Alternative splicing, posttranslational modifications, and regulation by auxiliary proteins have been proposed to contribute to this functional diversity (1,2,(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%